Development of high strength natural fibre based composite plates for potential application in retrofitting of RC structure - Alam M.A.; Alriyami K.; Jumaat M.Z.; Muda Z.C. (Indian Society for Education and Environment, 2023)
The potential application of green fibre based composite plate in retrofitting of structure is growing up in construction industry nowadays. The aim of this research was to develop high strength natural fibre based composite plates for the possible application in strengthening of reinforced concrete structure. The plates were fabricated using kenaf fibre, jute fibre and jute rope respectively. The fibres and rope were chemically treated using 6% NaOH solution to enhance the tensile strength of fabricated plates. In fabrication process, a special technique was applied to compact the treated and untreated fibres to obtain the highest tensile strength of composite plates. The physical and mechanical properties of the fabricated composite plates were then experimentally investigated. In general, results showed that the chemical treatments had an influence to enhance the tensile strength of the plates. The tensile strength of composite plates with treated kenaf fibre, jute fibre and jute rope were 137 MPa, 136 MPa and 113 MPa respectively. While those of untreated kenaf fibre, jute fibre and jute ropes were 131 MPa, 136 MPa and 110 MPa respectively. Kenaf and jute fibre composite plates had shown higher tensile strengths as compared to those of jute rope. The natural fibre composite plates were found to be linearly elastic in nature and had shown brittle failure. The moisture content and the water absorption of the plates with treated fibres were found to be lower as compared to those of untreated fibres. In terms of tensile strength of fabricated plates, kenaf, jute and jute rope composite plates could be used in retrofitting of structures.